(untitled) (Journal of Dhaka Medical College, 2023)
Background: Cerebral Palsy (CP), a complex neurodevelopmental disorder in children, is often accompanied by comorbidities like intellectual impairments besides core motor dysfunction. Aims: To assess the relationship between gross motor and intellectual functions among the children with CP. Methods: A cross- sectional study was carried out in the Institute of PaediatricNeurodisorder and Autism (IPNA), BSMMU, Dhaka, during Oct. 2017 to May 2018 including 82 children up to 12 years of age having CP. The gross motor function of all the children was evaluated using GMFCS. Psychological assessment was done by professional psychologist using age specific psychometric tools. Results: One third of the children (39.0%) belonged to age 2-4 years. Male to female ratio was 1.7:1. More than three fourths of the children (85.4%) were of term gestational age. Perinatal asphyxia (PNA) was associated in 92.7% children.More than half of the children (57.3%) had spastic quadriplegia. Almost half of the children (48.8%) GMFCS level was II and 28.0% children were of GMFCS level III. Nearly a half (48.8%) of the children was with mild intellectual impairment and 22.0% were with moderate intellectual impairment. There is a significant negative Spearman’s correlation (r=-0.639; p=0.001) between GMFCS level and intellectual level. Conclusion: More severe motor impairments in CP might be associated with higher intellectual dysfunction. J Dhaka Med Coll. 2021; 29(1): 9-15